Pemodelan Regresi Panel pada Data Pendapatan Asli Daerah (PAD) Terhadap Dana Alokasi Umum (DAU) - Caraka, Rezzy Eko (Jurnal Ekonomi Kuantitatif Terapan; 2019: Vol. 12, No.1, Februari 2019 (pp. 1-107), 2019)
Data panel is a composite of the data time series (over time) and cross section (between individuals / space). To describe briefly the data panel,egg in cross section,and the value of one or more variables were collected for the sample unit at a time of time. In panel data, the same cross section units surveyed in some time. Panel data regression was used to determine the most appropriate regression model is used to model local revenue (PAD) of the general allocation fund (DAU) for seven districts / cities in Central Java province from 2008 to 2010 budgets. Models produced by REM obtained R 2 values ??of 43.8893 % revenue (PAD) is influenced by the General Allocation Fund (DAU), while the rest influenced by other factors.
Keywords: Fixed Effect; Common Effect Model; Random Effect Model; PAD; DAU